Millennial‐Scale Vulnerability of the Antarctic Ice Sheet to Regional Ice Shelf Collapse - Stephen Cornford (Geophysical Research Letters, 2019)
The response of the Antarctic Ice Sheet to ice shelf collapse is explored with a high resolution ice sheet model. Rapid melting is applied to each of its major present day drainage basins in turn , to determine which parts of the ice sheet are most vulnerable to change in oceanic forcing, over the next 1000 years. We findthat West Antarctica can be largely deglaciated over a millenium, leading to more than two metres of sea level rise, if any of its major ice shelved disintegrated. The response of East Antarctica is more muted, but not negligible.